Thoracic Outlet Syndrome. Issue 4 (April 2015) - Kuhn, John E.; Lebus, George F.; Bible, Jesse E.
Abstract : Thoracic outlet syndrome is a well-described disorder caused by thoracic outlet compression of the brachial plexus and/or the subclavian vessels. Neurogenic thoracic outlet syndrome is the most common manifestation, presenting with pain, numbness, tingling, weakness, and vasomotor changes of the upper extremity. Vascular complications of thoracic outlet syndrome are uncommon and include thromboembolic phenomena and swelling. The clinical presentation is highly variable, and no reproducible study exists to confirm the diagnosis; instead, the diagnosis is based on a physician's judgment after a meticulous history and physical examination. Both nonsurgical and surgical treatment methods are available for thoracic outlet syndrome. Whereas nonsurgical management appears to be effective in some persons, surgical treatment has been shown to provide predictable long-term cure rates for carefully selected patients. In addition, physicians who do not regularly treat patients with thoracic outlet syndrome may not have an accurate view of this disorder, its treatment, or the possible success rate of treatment.